The impact of persistent social anxiety on social functioning and health‐related quality of life in young people with remitted first‐episode psychosis. Issue 8 (30th October 2021) - González‐Blanch, César; Gleeson, John F.; McEnery, Carla; O'Sullivan, Shaunagh; Ayesa‐Arriola, Rosa; D'Alfonso, Simon; Valentine, Lee; Tremain, Hailey; Bell, Imogen; Bendall, Sarah; Alvarez‐Jimenez, Mario
Abstract: Objective: Comorbid social anxiety is common in psychotic disorders and is associated with multiple negative consequences. However, the long‐term effects of persistent social anxiety versus fluctuating or no anxiety on social functioning and health‐related quality of life (HR‐QoL) have received scant attention. Therefore, we aimed to examine the prevalence of persistent social anxiety to determine its effect on social functioning and HR‐QoL in first‐episode psychosis (FEP). Methods: One hundred and eight individuals with remitted FEP were classified into three groups (persistent, fluctuating or no social anxiety) according to the Social Interaction Anxiety Scale over an 18‐month follow‐up period. The three groups were then compared at 18 months follow‐up to assess the influence of social anxiety on social functioning and HR‐QoL before and after controlling for confounders. Results: Of the 108 individuals with FEP, 25 (23.1%) had persistent social anxiety. This group presented lower social functioning and HR‐QoL levels compared to the groups with fluctuating or no anxiety symptoms. The effect on HR‐QoL remained significant after controlling for positive psychotic and depressive symptoms. Conclusions: In this study, nearly one‐quarter of young people with remitted FEP experienced persistent social anxiety symptoms, which had a negative impact on HR‐QoL. Thus, individuals with persistent social anxiety constitute a highly vulnerable group and may require targeted interventions to improve their social functioning and HR‐QoL.